2022
DOI: 10.5114/ada.2021.106021
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of repetitive paravertebral block with ropivacaine and dexmedetomidine for the prevention of postherpetic neuralgia in patients with acute herpes zoster

Abstract: Introduction Herpes zoster (HZ) is a disease caused by the reactivation of the varicella zoster virus. Postherpetic neuralgia (PHN) is the most common complication of HZ. Aim Repetitive paravertebral block with local anaesthetics and dexmedetomidine for the prevention of PHN in patients with acute herpes zoster. Material and methods 104 patients with acute herpes zoster were randomly divided into two groups. Group Rop received repetitive para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the past, several studies primarily focused on combining physical therapy and pharmacological interventions to treat ZRN or PHN patients (31,32). Our results suggested that the combination of two physical therapy similarly had a more satisfying effect and that all the three methods had positive effects, which may be attributed to the contribution of DRG to the occurrence and development of neuropathic pain (33,34).…”
Section: Discussionmentioning
confidence: 61%
“…In the past, several studies primarily focused on combining physical therapy and pharmacological interventions to treat ZRN or PHN patients (31,32). Our results suggested that the combination of two physical therapy similarly had a more satisfying effect and that all the three methods had positive effects, which may be attributed to the contribution of DRG to the occurrence and development of neuropathic pain (33,34).…”
Section: Discussionmentioning
confidence: 61%
“…In previous plane block and nerve block studies, it was found that the effect and duration of repeated blocks were longer [29,30]. Since we have observed that repeated blocks are associated with long-term efficacy, the blocks applied in our clinic are repeated three times.…”
Section: Discussionmentioning
confidence: 95%
“…73 Prevention of PHN, timely and effective pain control, and improvement of the patient's quality of life have become the focus of PHN interventions. 74,75 In recent decades, the standard treatment regimen for PHN has included the use of opioids, antiepileptics, and the addition of tricyclic antidepressants when necessary. 64,76 However, the above therapeutic effects remain controversial.…”
Section: Immunoprophylaxismentioning
confidence: 99%